Does the configuration of the street network influence where outdoor serious violence takes place?: using space syntax to test crime pattern theory - Summers, Lucia (Journal of quantitative criminology, 2017)
Objectives To examine the effect of the physical layout of the street network on the spatial distribution of outdoor serious violence. Crime pattern theory predicts crime would be more prevalent on more connected, accessible or traveled street segments, as these will be more likely to fall within an offender’s awareness space. Methods The distribution of incidents of outdoor murder, attempted murder and other near-lethal violent crimes that occurred in one London (UK) borough (N = 447 offenses) was analyzed. The space syntax methodology was used to estimate the to- and through-movement potential of individual street segments. Results Regression analyses showed higher levels of integration (a measure of to-movement potential) and choice (through-movement potential) were associated with greater odds of a street segment containing at least one crime. Risk was also higher for segments located near to segments with the highest global choice values. In contrast, connectivity (the number of other segments a street segment is adjacent to) was negatively associated with crime occurrence. Conclusions As predicted, the configuration of the street network was associated with the spatial distribution of outdoor serious violence. Crime reduction measures should be targeted at high-choice street segments (typically main arteries) and segments nearby.